Histórico de sofrimento psíquico em crianças de 2 a 4 anos: possíveis efeitos no desenvolvimento e na linguagem - Franco, Fernanda Nunes (2023)
The theme of this research was the relationship between the history of psychic suffering and effects on child development, in particular, on the process of language acquisition. This theme emerged from clinical observation and also the relationship between psyche and language explicited in the literature, especially in the early stages of development. Thus, the main objective of the research was to analyze the relationship between a history of psychic suffering and delay in language acquisition in children aged from two to four years old, who attended kindergarten in the city of Farroupilha (RS). The first stage consisted of sending a digital form that investigated basic data on the family and the child, as well as the response to the Child Development Risk Indicators in its questionnaire version (IRDI-Q), which was answered by 85 parents. In the second online stage of the research, 54 tests were sent for online response to the Dimensional Inventory for the Assessment of Child Development (IDADI), of which only 13 inventories returned. The 39 cases with a history of psychological distress, with 33 or more points, identified by the IRDI-Q, were invited to the second stage of the research, which was face-to-face. Only eight children attended this stage and the Labyrinth Scale was applied and, when necessary, IDADI data were complemented. Based on data from the first stage, a quantitative study was carried out in which sociodemographic variables, apgar data, data from playing, communication and language were analyzed in their association with the history of psychological distress. The results of the quantitative study showed that the history of psychological distress was not influenced by sociodemographic variables, nor was it associated with some aspects of child development, considering major language milestones and the beginning of symbolic play in the studied sample. There was only a tendency towards difficulty in socializing with other children in the group with a history of psychological distress when compared to the group without this history. In relation to the qualitative study with the eight children, it was evidenced that the evaluated children with a history of psychological distress showed delay in language acquisition and cognition, especially when they had higher scores on the IRDI-Q. In general, the third enunciative mechanism was more absent in interactions with the researcher, showing that even if there was typicality in major language milestones, the the constitution of the subject of discourse was difficult for these children. As a conclusion of the study, it can be said that the IRDI-Questionnaire is a viable instrument for assessing child development in the educational field, provided that it is accompanied by detailed and unique assessments of cases with a history of psychological distress, since there are cases in which there is overcoming of risk signs and others in which they produce effects on child development and language acquisition